Pembelajaran Bahasa Dalam Gamitan Pendidikan Karakter Dan Kurikulum Karakter - Nurazmi Br Siregar; Hamidah Sal’Aty; Nisa Amelia Purba; Harri Gusnirwanda (Universitas Dehasen Bengkulu, 2022)
This The purpose of this article is to understand how language learning in the lower grades of elementary school includes aspects of reading, writing, listening and speaking as well as to understand the importance of character education and Indonesian language learning which will be integrated in the teaching and learning process. The term learning is often heard in the study of education in schools today. This term is a development of the term